Modeling of the behavior of medium voltage insulators against lightning overvoltages - Shigihara, Miltom (2015)
Lightning causes important transient disturbances on transmission and distribution systems, with consequent damages to equipment, outages, and general decrease of the power quality. The assessment of the lightning dielectric strength of power equipment is generally based on tests performed using the standard lightning impulse voltage (1.2 / 50 µs waveshape), although the characteristics of the lightning overvoltages depend on many parameters and may vary widely. The behavior of insulators when subject to non-standard impulses depends both on the voltage amplitude and waveshape, and therefore a reliable model is required to produce the corresponding volt-time curves. Although there is no method universally accepted for this purpose, one of the most used is the Disruptive Effect (DE) model, which is based on the integration method concept. The application of this model involves the estimation of some parameters for which different procedures have been proposed in the literature, as for instance the procedures by Darveniza and Vlastos, by Hileman, by Chowdhuri et al., and by Ancajima et al. Tests of representative lightning overvoltages were performed to obtain the critical flashover overvoltages (CFO) and the volt-time curves of typical porcelain pin-type insulators considering three standard medium-voltage distribution classes (15 kV, 24 kV, and 36 kV) and five impulse voltage waveshapes, of both polarities. These tests provided data for the analyses of the insulators\' behavior and the results obtained using the different procedures for estimating the DE parameters. It is shown that in some cases insulator flashover is not predicted. A new method is then developed and proposed for evaluating the dielectric behavior of MV insulators. The method is validated using the typical insulators of the three voltage classes and the five lightning impulse voltages considered, of positive and negative polarities. The calculated volt-time curves showed in general a good agreement with the measured results for all the cases studied. The mean difference between the measured and calculated times to breakdown, for all the cases considered, was about 1.3 s; while the maximum difference was 4.0 s. The application of the proposed method to evaluate the occurrence of insulator flashovers in the shield wire line (SWL) system implemented in the State of Rondônia due to nearby lightning strikes supports previous conclusions that indicate that lightning has a significant impact on the SWL system performance in regions with high ground flash density.